A mimetic transpiration system for record high conversion efficiency in solar steam generator under one-sun. (June 2018) - Liu, Peng-Fei; Miao, Lei; Deng, Ziyang; Zhou, Jianhua; Su, Hui; Sun, Lixian; Tanemura, Sakae; Cao, Wenjiong; Jiang, Fangming; Zhao, Li-Dong
Abstract: Currently, direct solar steam generator based on suspending plasmonic solar absorber and floating porous photothermal convertors still suffered from high optical concentrations, poor productivity rates, high expenses and complicated fabrication processes. Here we designed a mimetic transpiration system imitating the water transport and transpiration of tree, the hydrophilic airlaid paper acting as the root of tree, the commercial expanded polyethylene foam as the soil for reducing the parasitic heat loss efficiently, and black carbonized wood with tremendous vertical channels as the photothermal convertor. A proof-of-concept mimetic transpiration system generator with carbonized wood achieved a record high conversion efficiency of 91.3% under one-sun, originating from the excellent thermal management of system and >97% carbonized wood solar absorptance and green house effect of vapor. Mimetic transpiration system can be fabricated by easy and scalable processes, providing a high-efficiency solar thermal conversion system for desalination, promising their industrial applications. Graphical abstract: Highlights: A mimetic transpiration system (MTS) for solar steam generation was designed. Completely carbonized wood slice (CW-S) with ordered macroporous severs as the absorber. The vertical channels of CW-S enhance the absorption of light and are beneficial to transportation of water. The MTS achieved record high conversion efficiency (91.3%) in solar steam generation under one-sun.